Shape controllers enhance the efficiency of graphene–TiO2 hybrids in pollutant abatement. Issue 6 (21st January 2016) - Sordello, F.; Odorici, E.; Hu, K.; Minero, C.; Cerruti, M.; Calza, P.
Abstract : The addition of graphene nanoplatelets (GNP) to TiO2 nanoparticles (NPs) has been recently considered as a method to improve the photocatalytic efficiency of TiO2 by favoring charge carrier separation. Abstract : The addition of graphene nanoplatelets (GNP) to TiO2 nanoparticles (NPs) has been recently considered as a method to improve the photocatalytic efficiency of TiO2 by favoring charge carrier separation. Here, we show that it is possible to improve the efficiency of GNP–TiO2 composites by controlling the shape, stability, and facets of TiO2 NPs grown on GNP functionalized with either COOH or NH2 groups, while adding ethylendiamine (EDA) and oleic acid (OA) during a hydrothermal synthesis. We studied the photocatalytic activity of all synthesized materials under UV-A light using phenol as a target molecule. GNP–TiO2 composites synthesized on COOH-functionalized GNP, exposing {101} facets, were more efficient at abating phenol than those synthesized on NH2 -functionalized GNP, exposing {101} and {100} facets. However, neither of these composites was stable under irradiation. The addition of both OA and EDA stabilized the materials under irradiation; however, only the composite prepared on COOH-functionalized GNP in the presence of EDA showed a significant increase in phenol degradation rate, leading to results that were better than those obtained with TiO2 alone. This result can be attributed to Ti–OH complexation by EDA, which protects GNP from oxidation. The orientation of the most reducing {101} facets toward GNP and the most oxidizing {100} facets toward the solution induces faster phenol degradation owing to a better separation of the charge carriers.